Characterization of a L136P mutation in Formin-like 2 (FMNL2) from a patient with chronic inflammatory bowel disease. - Raphael Trefzer (Public Library of Science (PLoS), 2021)
Diaphanous related formins are highly conserved proteins regulated by Rho-GTPases that act as actin nucleation and assembly factors. Here we report the functional characterization of a non-inherited heterozygous FMNL2 p.L136P mutation carried by a patient who presented with severe very early onset inflammatory bowel disease (IBD). We found that the FMNL2 L136P protein displayed subcellular mislocalization and deregulated protein autoinhibition indicating gain-of-function mechanism. Expression of FMNL2 L136P impaired cell spreading as well as filopodia formation. THP-1 macrophages expressing FMNL2 L136P revealed dysregulated podosome formation and a defect in matrix degradation. Our data indicate that the L136P mutation affects cellular actin dynamics in fibroblasts and immune cells such as macrophages.